Experimental investigation of isopropyl alcohol (IPA) /diesel blends in a diesel engine for improved exhaust emissions - Hazar, Hanbey; Uyar, Mahmut (My University, 2015)
This study focuses on the effect of blending isopropyl alcohol (IPA) and diesel fuel with conventionaldiesel. The effect of isopropyl alcohol on a diesel engine was examined experimentally in a three -cylinder direct injection diesel engine running at a constant speed of 1500 rpm at different loads. 1%dodecanol was added into the mixture. From the results, it was seen that the CO, HC and smoke densityemissions decreased, while NOx emissions and SFC increased with the increase in exhaust gastemperature.
Keywords: Mühendislik; Makine; Enerji ve Yakıtlar